Efeito da adição de háfnio na estrutura, resistência ao desgaste e oxidação a altas temperaturas em filmes finos de MoS2 - Silva Neto, Pedro Cardoso da (2019)
Solid particle erosion is common during the operation of equipment such as wind turbines, stationary turbines, aviation turbines, oil and steam pipelines, causing premature failure and damage. Protective coatings are commonly employed to reduce the damage caused by this type of wear but reports of the behavior of thin films of solid lubricants under these conditions have not been found in the literature. On the other hand, the advantages of using MoS2 lubricant thin films to increase the service life of wearable surfaces are well known, which may be indicative that these materials also perform well when subjected to other types of wear. In this way, the propose of this work was study the effects of Hf addition on the oxidation resistance, mechanical and tribological properties of MoS2 films containing different amounts of Hf. The results indicate the presence of the compound HfS3 in almost amorphous films, while the proposed erosion test methodology was compared with literature data. The erosion results show that a balanced composition between MoS2 and Hf favors erosion resistance at higher impact angles, while at the lower impact angles, films with more Hf have been shown to be more effective at resisting erosion.